Penerapan Teknik Latihan Penguatan Sendi pada Pasien dengan Gangguan Mobilitas Fisik di RSUD Bayu Asih Purwakarta - Ike Puspitaningrum; Fihinna khoerotun hisan (Jurnal Siti Rufaidah, 2026)
Physical mobility is highly influenced by the integrity of the musculoskeletal and neuromuscular systems, which play a fundamental role in facilitating body movement. Impairment in these systems, such as muscle weakness, limited joint range of motion, pain, or injury, may lead to decreased physical movement and functional limitations. This case study aimed to describe the implementation of joint strengthening exercise techniques in a patient with impaired physical mobility at RSUD Bayu Asih Purwakarta. Joint strengthening exercise techniques, as a nursing intervention, may improve joint flexibility and enhance physical mobility. This study employed a case study design using a comprehensive nursing care approach. Assessment findings revealed decreased extremity movement, reduced muscle strength, and limited joint range of motion. The nursing diagnosis established was impaired physical mobility. Nursing interventions were implemented through joint strengthening exercise techniques over three days in two sessions. Evaluation findings demonstrated partial improvement in extremity movement, muscle strength, and joint range of motion. The implementation of joint strengthening exercise techniques contributed to improved patient mobility; however, the problem of impaired physical mobility was not fully resolved, as the outcome indicators remained at scores of three to four, below the expected target score of five.